A novel synthetic oleanane triterpenoid, 2‐cyano‐3,12‐dioxoolean‐1,9‐dien‐28‐oic acid, regulates mechanical allodynia by rescuing neuronal cell death and glial cell activation in the spinal cord of resiniferatoxin‐treated rats - Ying‐Yi Lu; Chia‐Yang Lin; Hung‐Pei Tsai; Chih‐Lung Lin; Chieh‐Hsin Wu (Brain and Behavior, 2024)
Abstract Background Treating postherpetic neuralgia (PHN), which is characterized with a long‐lasting lancinating mechanical allodynia or hyperalgesia, is a big challenge as it is hard to achieve complete resolution. A synthetic triterpenoid, CDDO (2‐cyano‐3,12‐dioxoolean‐1,9‐dien‐28‐oic acid) can exert pleiotropic effects including anti‐inflammation and neuroprotective activities. Nevertheless, the antinociceptive effect of CDDO and its derivatives remains unknown. Resiniferatoxin (RTX) is easily feasible, and an RTX‐treated rodent model can mimic the PHN‐like symptoms. Therefore, RTX‐treated rats were used to serve as a PHN rats’ model in the study to elucidate whether a synthetic triterpenoid, CDDO, can improve mechanical allodynia in RTX‐treated rats. Methods The antinociceptive effects of CDDO were assessed by behavioral tests, western blotting, and immunohistochemistry. Paw withdrawal mechanical threshold was determined using calibrated forceps. Results Administration of RTX led to mechanical allodynia, neuronal cell death, and glial cell activation in the spinal cord of RTX‐treated rats. A synthetic triterpenoid, CDDO, blocked RTX‐induced mechanical allodynia, rescued neuronal cell death, and inhibited glial cell activation in the spinal cord of RTX‐treated rats. Conclusions Our study provides a novel result that a synthetic triterpenoid, CDDO, can interfere neuronal cell death and glial cell activation in the spinal cord of RTX‐treated rats. Hence, CDDO is an alternative therapeutic choice for PHN.